Impact of a Focused Approach for Discharge Teaching Regarding the Use of Aspirin as Anticoagulant After Joint Replacement Surgery. (July 2015) - Wittig-Wells, Deborah; Higgins, Melinda; Davis, Erica; Johnson, Ifeya; Louis, Latalya; Mason, Olga; Samms-McPherson, Jacqueline; Sims, Sandra; Jacob, Ani
<x xml:space="preserve">Abstract</x> BACKGROUND: Patient education for the use and administration of aspirin (ASA) as an anticoagulant may be deficient. PURPOSE: To pilot a knowledge assessment tool regarding the use of aspirin (ASA) as an anticoagulant and to evaluate the impact of a focused approach for discharge teaching. DESIGN: One-group pretest–posttest pilot study. SAMPLE: Convenience sample of patients hospitalized for total knee and total hip arthroplasty. MEASURE: Researcher developed ASA quiz. INTERVENTION: Focused education on aspirin as an anticoagulant. RESULTS: There was a statistically significant improvement in knowledge (Wilcoxon rank sum test Z = 3.880, p < .001).